Romanian naval diplomacy, continuous evolution in the swirl of external diplomacy - Moise, Ioan Gabriel; Kaiter, Edith-Hilde (Technium Sustainability, 2022)
From ancient times the dominion of the seas has been a condition for gaining power and influence, and the position of a state near a sea has been an advantage for both its development and the neighboring region. Due to its geographical position, the Black Sea is a region of great importance for all actors claiming leading positions in the world hierarchy and the intensification of economic relations between the states of the region after the end of the Soviet monopoly and its connection to the world market generated auspices for a new cycle development and regional prosperity. The relocation of the EU border to the Black Sea, along with the integration of Romania and Bulgaria, brings in many economic benefits, given its dependence on oil imports, but its expansion, like that of NATO, does not only mean benefits. The EU and NATO must also take on vulnerabilities in the area, such as underperforming economies, arms, drug and human trafficking, illegal immigration or frozen conflicts, and thus try to help stabilize the region. In recent years, the military has not only played a destabilizing role, but has made a decisive contribution to ensuring the security of the Black Sea region. In this sense, the military naval forces of the riparian countries, including Romania, had a special role. Through the wide range of missions in which the Romanian Naval Forces participate in the Danubian-Pontic space, both internally and externally, in cooperation with the states bordering the Black Sea and with the NATO member states, Romania contributes to the promotion of regional security and stability. The naval diplomacy actions carried out in the last thirty years thus reveal not only the role and purpose of the Romanian Naval Forces within NATO in the actions of maintaining and consolidating good relations with the states bordering the Black Sea, as well as maintaining security with allies in the distant maritime districts. They also point out that naval diplomacy has contributed to the expression of foreign policy in different areas and with means that have increased its effect, impact and efficiency.